THE THE IMPORTANCE OF CARE AND PREVENTION WITH COVID-19 IN THE WORK ENVIRONMENT - Yamada Rodrigues, Patrícia; Rodolpho, Daniela (Revista Interface Tecnológica, 2022)
This article presents as theoretical foundation the bibliographic, qualitative and descriptive research, given that the subject addressed, seeks to present in a very succinct way the main changes in the work environment caused by COVID-19 and, as they are essential in contemporary society. and they are present even in our daily lives even if they end up going unnoticed. The work aims to analyze and discuss the main concepts about the virus and the care that need to be taken mainly in the work environment as it has been perceived in different countries of the world, which are widely disseminated and explored by all, it is structured as follows way: definition, a brief history, the main discoveries, how their classification is organized according to the competent bodies, the national legislation related to equipment with such specificities; so that workers can increasingly develop their potential without neglecting their health and their correlates at work, thus becoming an integral part of a collaborative, committed and healthy society. In short, the intention of this article is to collaborate with aspects for reflection and search for new paths, new perspectives, for the advancement of public policies, research, development of a healthier work environment..
Keywords: Selecionado:Pandemic; Equipments; Legislation